PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN FISIK DI KEPENGHULUAN BANGKO PUSAKA KECAMATAN BANGKO PUSAKO KABUPATEN ROKAN HILIR - Lubis, Bayu Sapta Jaya; ", Mayarni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Community Participation in Physical Development in Kepenghuluan Bangko Pusaka Bangko Pusako Heritage District of Rokan Hilir. Adviser : Mayarni. Community participation in development is the participation of the community in the development process either in the planning stages of development through musrenbangkep, the implementation phase of development, to evaluate the development and benefit the development. Community participation in development planning through development planning meetings (musrenbang) is still minimal and passive, this was due to lack of public understanding of the development planning, low levels of education, and lack of socialization of the then government did not include the community in development planning.The concept of the theory used is participation. Researchers used Soetomo theory. This study aims to determine how the public's participation in physical development in Kepenghuluan Bangko Pusaka Bangko Pusako Heritage District of Rokan Hilir. This study uses qualitative research methods with an assessment of descriptive data. In collecting the data the researcher used interview, observation and documentation. By using key informants as a source of information.The results showed that participation in physical development is still very minimal and passive, meaning that there are still many people who are not involved in any stage of development to be carried out and they handed over all decisions to the other party. In this case the researchers advise people to participate actively in every stage of development and the government should also seek more public participation and active for the idea / ideas that come from the community more so that it can be considered as well as the evaluation for the next year.Keywords: Participation, Community, Development